Wage gaps, hysteresis and structural unemployment: The West German labour market in the seventies and eighties - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
In recent years, there has been an intense debate among economists about the causes of unemployment in Europe. Broadly speaking, the views can be grouped into two familiar camps: those with a more (neo-)classical outlook - stressing the importance of factor price movements, institutional rigidities and structural change - and those with a more Keynesian leaning, focusing on the restrictive fiscal policy stance in Europe or the long-term hyster- 2) esis effects of the worldwide recession of 1981-82. Lately, a new intermediate position has been added by Fitoussi, Phelps (1988), who point to the crowding-out of investment in Europe through the peculiar American policy mix of the eighties, thus making the United States the culprit of Europe's malaise. All major Keynesian positions (and also the one by Fitoussi, Phelps) rely on the tacit, but crucial assumption that - by and large - the unemployment of the eighties is an analytically new phenomenon to be explained separately from the experience of the seventies which is by now grudgingly admitted to have been a period of more classical than Keynesian unemployment. It is the purpose of this paper to show that this assumption is not warranted so that, at least in some important respectsj the eighties are simply the natural continuation and maybe culmination of developments which go back to the seventies. Empirically, we shall make our case for one country only, the Federal Republic of Germany, but similar lines of reasoning may apply to other EEC countries, of course with proper adjustments and qualifications.
Keywords: 330; Arbeitslosigkeit; Strukturelle Arbeitslosigkeit; Lohn; Arbeitsmarkt; Hysteresis; Deutschland